Pengaruh Technological Capital dan Spiritual Capital terhadap Kinerja Perusahaan - Siti Nafisah Azis (Jurnal Riset Akuntansi, 2026)
Company investment in intangible assets in the form of intellectual capital such as technological capital and spiritual capital is still considered an alternative option in improving company performance. However, in the era of digital transformation and value-based management, these forms of capital are increasingly important for organizational sustainability and competitiveness. This study aims to determine the effect of technological capital and spiritual capital on company performance. The study employed a quantitative research approach, involving 37 employees as selected respondents. The data used were primary data collected through a structured questionnaire developed to measure each variable in the study. The data were processed using SmartPLS 4 to evaluate validity and reliability, and to analyze the structural relationships between the variables. The results of this study indicate that technological capital has a positive and significant effect on company performance, and spiritual capital also has a positive and significant effect on company performance. These findings provide empirical evidence that increasing investment in technological capital and spiritual capital can enhance company performance, both financially and non-financially.